2018
DOI: 10.1589/jpts.30.216
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the extent of utilization of physiotherapy services by physicians in Saudi Arabia

Abstract: [Purpose] To investigate physicians’ attitudes, opinions and experiences towards physiotherapy services as well as to identify the potential factors that may affect the extent of utilization of physiotherapy services (based on physicians’ beliefs) in Saudi Arabia (SA). [Subjects and Methods] A cross-sectional study was conducted. [Results] A total of 108 respondents met the inclusion criteria. The respondents’ attitude towards physiotherapy was slightly low (53.5%), while their opinions and experiences of phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The low utilization of rehabilitation services is a great concern considering that KZN has a high burden of non-communicable diseases, injury, TB and HIV which has an impact on the need for rehabilitation services (KZN, 2015). Previous studies reported low utilization and accessibility of rehabilitation services (Leitarts, 2014;Alshehri, 2018). The low utilization of rehabilitation services could be attributed to a lack or awareness of rehabilitation coupled with poor referral systems and to prejudices associated with rehabilitation services (Leitarts, 2014;Adam, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The low utilization of rehabilitation services is a great concern considering that KZN has a high burden of non-communicable diseases, injury, TB and HIV which has an impact on the need for rehabilitation services (KZN, 2015). Previous studies reported low utilization and accessibility of rehabilitation services (Leitarts, 2014;Alshehri, 2018). The low utilization of rehabilitation services could be attributed to a lack or awareness of rehabilitation coupled with poor referral systems and to prejudices associated with rehabilitation services (Leitarts, 2014;Adam, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that only approximately one-third of medical doctors referred cases to a physiotherapist. A study conducted in Saudi Arabia of 108 physicians about their perception of physical therapy services reported that physiotherapists lack knowledge and skill to assess and treat patients ( Alshehri et al, 2018 ). A study conducted among 282 patients with peripheral vestibular disease reported an average of late medical consultation after months or years from the onset of symptoms ( Jáuregui-Renaud et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Physiotherapists are caring for recovering patients in all stages of their rehabilitation, whether acute, subacute, or long-term. 2 Students of physical therapy have a lot to offer as well by volunteering in hospitals and maintaining public health. Our intent was to explore the extent to which the students are actively involved in managing their own and their family's health, which is vital during this pandemic.…”
Section: Introductionmentioning
confidence: 99%